Metasurfaces: An Acoustic Meta‐Skin Insulator (Adv. Mater. 37/2020). Issue 37 (15th September 2020) - Tong, Lei; Xiong, Zhu; Shen, Ya‐Xi; Peng, Yu‐Gui; Huang, Xin‐Yu; Ye, Lei; Tang, Ming; Cai, Fei‐Yan; Zheng, Hai‐Rong; Xu, Jian‐Bin; Cheng, Gary J.; Zhu, Xue‐Feng
Abstract : In article number 2002251, Lei Ye, Hai‐Rong Zheng, Jian‐Bin Xu, Gary J. Cheng, Xue‐Feng Zhu, and co‐workers implement a microstructured meta‐skin insulator to reflect acoustic waves in an all‐angle and wide spectrum range, due to the tremendous impedance mismatch at the superhydrophobic air/water interface. This strategy in particular, has application potential for underwater acoustic metamaterials, since the detrimental solid–fluid coupling can be substantially diminished by coating the metaskin insulator on the designed metastructure.